2017
DOI: 10.1167/iovs.17-22200
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Protects Retinal Ganglion Cells Against Glaucomatous Injury In Vitro and In Vivo

Abstract: H2S is specifically regulated in experimental glaucoma. By scavenging reactive oxygen species and dilating retinal vessels, H2S may protect RGCs from pressure and oxidative stress-induced RGC loss in vitro and in vivo. Therefore, H2S might be a novel neuroprotectant in glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 27 publications
0
37
0
1
Order By: Relevance
“…Zur Darstellung der Gefäße der Retina wurden kurz vor der Kauterisation der Tiere OCT-Aufnahmen (OCT: optische Kohärenztomografie) des operierten Auges mit dem Spectral-Domain-OCT (SD-OCT; Heidelberg Engineering; Heidelberg) angefertigt, wie in folgenden Studien zuvor [20,21]. Damit die Darstellung der Gefäße optimal ist, trugen alle Ratten während der Untersuchung entsprechend angepasste Sammellinsen.…”
Section: Oct-untersuchungunclassified
“…Zur Darstellung der Gefäße der Retina wurden kurz vor der Kauterisation der Tiere OCT-Aufnahmen (OCT: optische Kohärenztomografie) des operierten Auges mit dem Spectral-Domain-OCT (SD-OCT; Heidelberg Engineering; Heidelberg) angefertigt, wie in folgenden Studien zuvor [20,21]. Damit die Darstellung der Gefäße optimal ist, trugen alle Ratten während der Untersuchung entsprechend angepasste Sammellinsen.…”
Section: Oct-untersuchungunclassified
“…Recently, there have been questions whether any such effect of H 2 S could be applicable in glaucoma. Therefore it has been tested in some previous studies …”
Section: Introductionmentioning
confidence: 99%
“…Therefore it has been tested in some previous studies. [16][17][18][19][20] Apoptosis is essential in normal development for the maintenance of tissue homeostasis. 21,22 The process of apoptosis induction mechanism is initiated by several factors, including decrease in growth factors and DNA damage.…”
mentioning
confidence: 99%
“…Alteration of endogenous H 2 S level in retina is correlated with different pathological situations, and its exogenous donors exhibited potential in protecting retinal ganglion cells against assaults, such as diabetic retinopathy, ischemia-reperfusion injury, and N-methyl-Daspartic acid-(NMDA-) induced excitatory neurotoxicity [16][17][18]. In our previous study, alteration of endogenous H 2 S synthases is observed in a glaucoma animal model; furthermore, we observed that GYY4137, a slow-release H 2 S donor, effectively protected RGCs against different glaucomatous injuries in vitro and in vivo [19].…”
Section: Introductionmentioning
confidence: 99%